PENGARUH PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB PP) DAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA 3 DAERAH - Martha Agustina Matanari; Harlyn L. Siagian (Program Studi Magister Manajemen Universitas Advent Indonesia, 2022)
Abstract : The author aims to see how the influence of PBB PP, BPHTB on PAD. The data used in this study is secondary data taken from information on financial realization reports from 3 regions, namely Medan City, Binjai, Pematangsiantar for the 2017-2021 period. The data processing technique used is the Classical Assumption Test, T test, F test and the coefficient of determination (R2) using the SPSS version 26 application. The data used in this study passed and met the requirements of the Classic Assumption Test. Based on the results of descriptive statistics from the three regions studied, the city of Medan has the maximum value in the PBB PP, BPHTB and PAD variables. With the T test, it was found that PBB PP had a positive and significant effect, seen from the PBB PP variable having a significance value of 0.000 or <0.05, which means that there was an influence on the acceptance of PBB PP (X1) there was pad (Y). And when viewed from Tcount 8.373 it is greater than Ttable 2.17881 which means that pbb pp (X1) indicates an influence on pad (Y). And also the BPHTB variable has a significance value of 0.000 or not greater than 0.05, which means that there is an effect of BPHTB acceptance (X2) on the pad (Y). And when viewed from the Tcount value of 5.950, it is greater than Ttable 2.17881 which means that there is an effect of BPHTB acceptance (X2) on the pad (Y). Simultaneously it was found that the significance value of 0.000 or < 005 means that the variables pbb pp (X1) and bphtb (X2) simultaneously have a significant effect on the pad variable (Y). And Fcount is 1301.732 or > Ftable 3.89, meaning that the variable pbb pp (X1) and bphtb (X2) simultaneously affect the variable pad (Y).